The linguistic features of English used by UiTM teaching English as a second language (TESL) students in their facebook interactions / Noorzaina Idris - Idris, Noorzaina (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Facebook is a popular social network which has become a powerful and essential tool for communication today. This study examines the use of English in the Facebook interactions of TESL (Teaching English as a second language) students in the Faculty of Education, UiTM Shah Alam, Malaysia using the categories adapted from Thurlow and Brown (2003) and McNeil (2008). The study also addresses the respondents’ perceptions on their language choice and language use using the survey questions and interviews. This study is significant as it provides empirical evidence of the use of English in social media in a Malaysian context. The findings indicate that there are several features of English used in their Facebook interactions which show that a distinct variety of English is used in this computer-mediated context. This is because there is frequent use of non-standard forms of English where some words are abbreviated and spelt in non-conventional spelling. Although these students are TESL students, they believe that it is acceptable to use these non-standard forms because their written texts in Facebook are not considered as academic writing. They are writing in such a way because they are communicating, adapting and accommodating their "speech” in the written mode in online communication.